2012
DOI: 10.1155/2012/287438
|View full text |Cite
|
Sign up to set email alerts
|

Social Activity and Cognitive Functioning Over Time: A Coordinated Analysis of Four Longitudinal Studies

Abstract: Social activity is typically viewed as part of an engaged lifestyle that may help mitigate the deleterious effects of advanced age on cognitive function. As such, social activity has been examined in relation to cognitive abilities later in life. However, longitudinal evidence for this hypothesis thus far remains inconclusive. The current study sought to clarify the relationship between social activity and cognitive function over time using a coordinated data analysis approach across four longitudinal studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 51 publications
(60 reference statements)
3
55
4
1
Order By: Relevance
“…However, the evidence of positive effects of cognitive engagement on cognitive change is inconsistent (Jak, 2012; Lövdén, Xu, & Wang, 2013). Greater cognitive activity and higher educational attainment, while being associated with better concurrent cognitive test scores, does not slow declines in cognitive performance (Brown et al, 2012; Vaughan et al, 2014; Zahodne et al,2011). Moreover, the benefits of cognitive and social engagement may be attenuated in healthy persons with high education (Vemuri et al, 2014), such as the participants of our study, and are quite modest even in an unselected community sample (Haslam, Cruwys, & Haslam, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…However, the evidence of positive effects of cognitive engagement on cognitive change is inconsistent (Jak, 2012; Lövdén, Xu, & Wang, 2013). Greater cognitive activity and higher educational attainment, while being associated with better concurrent cognitive test scores, does not slow declines in cognitive performance (Brown et al, 2012; Vaughan et al, 2014; Zahodne et al,2011). Moreover, the benefits of cognitive and social engagement may be attenuated in healthy persons with high education (Vemuri et al, 2014), such as the participants of our study, and are quite modest even in an unselected community sample (Haslam, Cruwys, & Haslam, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Some individual studies have shown that social activities, larger social networks, and a history of social contact are associated with better cognitive function and reduced risk for cognitive decline [92][93][94][95][96][97][98][99][100][101]. However, an independent coordinated analysis of four longitudinal studies found no effect on cognitive functioning [102]. Looking at the totality of the evidence, most studies in this area are small, are combined with cognitive training and/or physical activities (making it difficult to disaggregate the potential benefits solely of social engagement), and/or are too dissimilar in types of social engagement to draw any conclusions.…”
Section: Social Engagementmentioning
confidence: 99%
“…1822 There is a concern that positive associations have been observed previously because early cognitive decline may lead to social isolation (reverse causation). 23 Therefore, it may be important to use sensitive measures of cognition at study baseline in order to exclude participants with subtle cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%